Pengaruh Kualitas Pengungkapan Corporate Social Responsibility, Dewan Direksi Wanita Dan Dewan Komisaris Wanita Terhadap Tax Aggressive - Beni Rahman; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2020)
The objective of this study is to examine the effect of quality of corporate social responsibility disclosures, female board of directors and female board of commissionerss on tax aggressive. The analysis technique used multiple regression analysis methods. The sample for this study consisted of 19 companies listed on the Indonesia stock exchange (BEI) and reported sustainability reports for 2015-2018, so that 76 observations were obtained. The results found that quality of CSR disclosure has no effect on tax aggressive, the female board of directors has no effect on tax aggressive. While the female board of commissioners has negative effect on tax aggressive. Future researches are sugested to focus on each company to get better results.